RANCANG BANGUN SISTEM PENENTUAN STATUS GIZI BALITA DENGAN METODE K-MEANS - Sucipto , Hadi; Faizah , Arbiati (Inovate, 2019)
Malnutrition or also called malnutrition is still a problem in Indonesia, especially in the toddler agegroup. Lack of nutritional intake at an early age will have a negative impact on the growth anddevelopment of infants, which will further hamper some of the developmental processes of the toddler,such as learning to talk, walk, eat, and other activities. In this study the design of the nutritional statusdetermination system for toddlers is discussed using the K-Means method. The data will be groupedinto six clusters, namely baduta or under-fives, under-five or under-five, under-five or under-line(BGM), under-five or under-five, under-five or fat under-five, and under-five or under-five. By usingthe K-Means method, the data of children under five or under two years will be grouped into clustersthat have been determined. The results of this study are the design of a system for determining thenutritional status of children under five in the form of a clustering system for the nutritional status ofchildren with an effective level of valid data from the implementation of a design system fordetermining the status of a toddler with the K-Means Method is 77.3 percent.Keywords: Cluster, K-Means, Nutrition, Toddler .